2008
DOI: 10.1086/528718
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-Onset Primary Cytomegalovirus Disease and the Risk of Allograft Failure and Mortality after Kidney Transplantation

Abstract: This study of a large cohort of CMV-seronegative recipients of kidney transplants from CMV-seropositive donors illustrates the ongoing challenge of delayed-onset primary CMV disease and its impact on transplantation outcomes despite antiviral prophylaxis. Better strategies for CMV disease prevention after kidney transplantation are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
208
4
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(227 citation statements)
references
References 36 publications
6
208
4
4
Order By: Relevance
“…Through direct, indirect and possibly immunomodulatory mechanisms, CMV is an important predictor of mortality after transplantation [20,32,33] . Prior to the availability of intravenous (IV) and oral ganciclovir, CMV was a major cause of mortality after liver transplantation.…”
Section: Impact On Mortalitymentioning
confidence: 99%
“…Through direct, indirect and possibly immunomodulatory mechanisms, CMV is an important predictor of mortality after transplantation [20,32,33] . Prior to the availability of intravenous (IV) and oral ganciclovir, CMV was a major cause of mortality after liver transplantation.…”
Section: Impact On Mortalitymentioning
confidence: 99%
“…First, a significant number of patients (approximately 20-30% of Dþ/RÀ patients) may still develop CMV disease after discontinuation of prophylaxis (15,16). This is termed ''late-onset CMV disease'' and some studies suggest that it remains associated with poor outcomes in SOT recipients (17,18). Second, the preemptive approach, by allowing low-grade viral replication during the early posttransplant period, may not appropriately prevent the occurrence of CMV-associated indirect effects, and therefore long-term transplant outcomes might be inferior as compared to patients receiving antiviral prophylaxis (11).…”
Section: Introductionmentioning
confidence: 99%
“…Because EOD occurs mainly after a preemptive strategy, we believe that this strategy is not appropriate in D+RÀ patients and argue strongly for universal prophylaxis in these high-risk patients. Moreover, in na€ ıve D+/RÀ patients, universal prophylaxis is thought to hamper the development of a specific immune response, causing more late-onset CMV infections than the preemptive approach (3,39), with increased morbidity (10). This observation could argue for the choice of a preemptive strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In one study directly comparing prophylactic and preemptive approaches, it was clearly demonstrated that late DNAemia occurs much more frequently in the prophylactic versus the preemptive setting (3,4). In addition, late DNAemia has been associated with poor prognosis, with a reduction in graft survival and higher patient mortality (5)(6)(7)(8)(9)(10). Moreover, it has been claimed that the preemptive strategy, usually associated with CMV DNAemia or early onset disease (EOD), may have the advantage of boosting antiviral immunity by exposure to asymptomatic DNAemia compared with universal prophylaxis (11).…”
Section: Introductionmentioning
confidence: 99%